0181 Comparison of cadaver types for spinal surgery training. (2nd November 2015) - Tomlinson, James; Yiasemidou, Marina; Roberts, Dave; Timothy, Jake
Abstract : Background: Spine pedicle screw insertion is technically demanding, with potentially serious risks if screws are misplaced, and an established learning curve of approximately 70 screws placed before there is a significant reduction in screw misplacement. Despite this most units continue to teach screw insertion for the first time in live surgery, both in the UK and worldwide. This study was a single blinded comparison of cadaver types to simulate screw insertion. Methodology: Three cadaver types – Thiel, Crosado and Formaldehyde were positioned prone and a posterior approach to the spine performed. The spines were all exposed by a single surgeon. Experienced spinal surgeons placed screws in each cadaver type sequentially and gave feedback on the tissue quality and feel using a modified Likert scale. Results: Thiel cadavers rated most highly for soft tissue feel and appearance with a median score of 6. Crosado cadavers rated most highly for bony properties, with a median score of 6. Formaldehyde cadavers rated poorly for soft tissue feel, appearance and bony qualities with median scores of 2, 2.5 and 3.5 respectively. Conclusions: There is a strong argument that pedicle screw insertion should be taught away from the operating theatre but this will have significant cost implications. Cadaveric screw simulation offers the most realistic simulation, with Thiel and Crosado cadavers both rating highly for their properties. Further work is now needed on a larger scale to further explore this valuable resource in surgical training. References: Bergeson RK, Schwend RM, DeLucia T, Silva SR, Smith JE, Avilucea FR. How accurately do novice surgeons place thoracic pedicle screws with the free hand technique? Spine 2008;33(15):E501–7 Gonzalvo A, Fitt G, Liew S, et al . The learning curve of pedicle screw placement: how many screws are enough? Spine 2009;34(21):E761–5 Gautschi OP, Schatlo B, Schaller K, Tessitore E. Clinically relevant complications related to pedicle screw placement in thoracolumbar surgery and their management: a literature review of 35, 630 pedicle screws. Neurosurg Focus 2011;31(4):E8